2016
DOI: 10.1016/j.jval.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Which Questionnaire Should Be Used to Measure Quality-of-Life Utilities in Patients with Acute Leukemia? An Evaluation of the Validity and Interpretability of the EQ-5D-5L and Preference-Based Questionnaires Derived from the EORTC QLQ-C30

Abstract: Although the Quality of Life Questionnaire Preference-Based Measure and the EORTC-8D appear to have better validity, this study does not provide any strong evidence against the use of the EQ-5D-5L for measuring quality-of-life utilities in acute leukemia. However, our findings need to be confirmed in larger longitudinal studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…In their analysis of data from a large population-based cancer cohort, Lorgelly et al [9] found that the two instruments showed high correlation but poor agreement. As in our study, van Dongen-Leunis et al [31] found that PBM derived from the EORTC-QLQ30 and the EQ-5D-5L showed good convergent and known groups' validity in acute leukemia patients, though the disease-specific PBM showed greater discriminatory power than EQ-5D-5L. In multiple myeloma patients, Rowen et al [32] found that EORTC-8D utility estimates were broadly comparable to those obtained using EQ-5D, but that EORTC-8D better captured changes in HRQOL patients in mild health states.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In their analysis of data from a large population-based cancer cohort, Lorgelly et al [9] found that the two instruments showed high correlation but poor agreement. As in our study, van Dongen-Leunis et al [31] found that PBM derived from the EORTC-QLQ30 and the EQ-5D-5L showed good convergent and known groups' validity in acute leukemia patients, though the disease-specific PBM showed greater discriminatory power than EQ-5D-5L. In multiple myeloma patients, Rowen et al [32] found that EORTC-8D utility estimates were broadly comparable to those obtained using EQ-5D, but that EORTC-8D better captured changes in HRQOL patients in mild health states.…”
Section: Discussionsupporting
confidence: 83%
“…Although this is the first study to compare the performance of EQ-5D-5L with the FACT-8D, other studies have compared the performance of EQ-5D with the EORTC-8D, a cancer-specific PBM scored from the EORTC QLQ-C30 questionnaire [9,31,32]. In their analysis of data from a large population-based cancer cohort, Lorgelly et al [9] found that the two instruments showed high correlation but poor agreement.…”
Section: Discussionmentioning
confidence: 94%
“…Disease-specific instruments like the European Organization for Research and Treatment of Cancer Quality of Life Core Questionnaire 30 (EORTC QLQ-C30), Medical Research Council/EORTC Quality of Life Questionnaire Leukemia Module (MRC/EORTC QLQ-LEU), Functional Assessment of Cancer Therapy-General (FACT-G) and the Functional Assessment of Cancer Therapy-Leukemia(FACT-Leu) are commonly used to measure the HRQoL of patients with leukemia [ 6 10 ]. While they are valid and reliable, they cannot be used to generate health utility value for leukemia patients because they are not preference-based instruments [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ever since, scoring algorithms of EQ-5D-5L based on the general public’s health preferences were developed in many countries such as China [ 18 ], the UK [ 19 ] and Germany [ 20 ]. While EQ-5D-5L has been applied to cancer patients [ 11 ], It is rarely used to measure health status and health utility of patients with leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…Preference‐based HRQoL measures are actively used as well in clinical studies, for example, among persons with type 2 diabetes, chronic obstructive disease in the lungs, asthma, and cardiovascular diseases (van Hout et al., ). Most frequently used are the preference‐based measures of health from the Short Form‐36 (Brazier, Roberts, & Deverill, ); the European Quality of Life, 5‐domain survey (van Dongen‐Leunis, Uyl‐de, & Groot, ; Kind, ); and the Health Utilities Index Mark 2, 3 (HUI 2, 3) (Hays et al., ; Horsman, Furlong, Feeny, & Torrance, ). Previously conducted were studies confirming the lack of significant differences in evaluating HRQoL with these tools (Herschorn, Kaplan, Sun, & Ntanios, ).…”
Section: Introductionmentioning
confidence: 99%